2020
DOI: 10.1162/dint_a_00055
|View full text |Cite
|
Sign up to set email alerts
|

The Computer Science Ontology: A Comprehensive Automatically-Generated Taxonomy of Research Areas

Abstract: Ontologies of research areas are important tools for characterizing, exploring, and analyzing the research landscape. Some fields of research are comprehensively described by large-scale taxonomies, e.g., MeSH in Biology and PhySH in Physics. Conversely, current Computer Science taxonomies are coarse-grained and tend to evolve slowly. For instance, the ACM classification scheme contains only about 2K research topics and the last version dates back to 2012. In this paper, we introduce the Computer Science Ontol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 35 publications
0
39
0
1
Order By: Relevance
“…The restriction of the set of considered publications according to their research areas as revealed in citation indexes or through the analysis of author keywords allows refining the creation and validation of knowledge graphs by eliminating outputs outside the scope of the developed resource (Salatino et al, 2020). This prevents the overlapping of concepts from different fields when they are represented by the same polysemous term and consequently eliminates noise from the generated database.…”
Section: Other Metadatamentioning
confidence: 99%
“…The restriction of the set of considered publications according to their research areas as revealed in citation indexes or through the analysis of author keywords allows refining the creation and validation of knowledge graphs by eliminating outputs outside the scope of the developed resource (Salatino et al, 2020). This prevents the overlapping of concepts from different fields when they are represented by the same polysemous term and consequently eliminates noise from the generated database.…”
Section: Other Metadatamentioning
confidence: 99%
“…AIDA was generated using an automatic pipeline that integrates and enriches data from Microsoft Academic Graph, Dimensions, Global Research Identifier Database, DBpedia, CSO [14], and INDUSO. It consists of three steps: i) topics detection, ii) extraction of affiliation types, and iii) industrial sector classification.…”
Section: Aida Generationmentioning
confidence: 99%
“…4M articles and 5M patents are also classified according to the type of the author's affiliations (academy, industry, or collaborative) and 66 industrial sectors (e.g., automotive, financial, energy, electronics) obtained from DBpedia. AIDA was generated by integrating several knowledge graphs and bibliographic corpora, including Microsoft Academic Graph (MAG), Dimensions, English DBpedia [8], the Computer Science Ontology (CSO) [14], and the Global Research Identifier Database (GRID) 8 . It can be downloaded for free from the AIDA website 9 under the CC BY 4.0 license.…”
Section: Introductionmentioning
confidence: 99%
“…We also mapped the CSO topics to the Fields of Study (FoS) concepts reseased by Microsoft Academic. More details regarding the alignment between CSO and other knowledge bases are avaliable in Salatino et al [26].…”
Section: Computer Science Ontologymentioning
confidence: 99%
“…In this chapter, we present the Computer Science Ontology (CSO) Framework [27,26], which is a conceptual framework for generating a large scale ontology of Computer Science. This solution has been used to support a variety of high-level tasks, such as (i) categorising proceedings in digital libraries, (ii) enhancing semantically the metadata of scientific publications, (iii) generating recommendations, (iv) producing smart analytics, (v) detecting research trends, and others [20,27].…”
Section: Introductionmentioning
confidence: 99%